2015
DOI: 10.4236/ojf.2015.54027
|View full text |Cite
|
Sign up to set email alerts
|

Stand Structure, Diversity and Regeneration Status of Woody Species in Open and Exclosed Dry Woodland Sites around <i>Molapo</i> Farming Areas of the Okavango Delta, Northeastern Botswana

Abstract: Stand structure, diversity and regeneration status of woody species were investigated in open and exclosed dry woodland sites in Island Safari, Shorobe and Xobe, northeastern Botswana. A total of 105, 111 and 130 quadrats, measuring 20 × 20 m each, were laid down along parallel line transects in the three sites, respectively, to collect data. A total of 47 species, representing 16 families and 24 genera, were recorded in the study sites. Of these, 33 species representing 13 families and 20 genera, 41 species r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 42 publications
6
39
0
3
Order By: Relevance
“…O treinamento e aplicação das redes ao conjunto de validação foram realizados com 10 repetições, onde no início de cada treinamento eram utilizados pesos iniciais aleatórios nas conexões dos neurônios da rede. RESULTADOS E DISCUSSÃO A distribuição média da probabilidade observada por classe de diâmetro apresentou forma exponencial negativa (J invertido), sendo as classes de menores diâmetros com maior probabilidade de ocorrência dos indivíduos, típica de florestas inequiâneas (NEELO et al, 2015;JIMENEZ et al, 2016). Conforme esperado, as classes diamétricas inferiores apresentaram maior amplitude de valores de probabilidade em relação às classes superiores, no entanto, quando é feita a razão pela média da classe, nota-se maior variação nestas últimas (Figura 2).…”
Section: Função De Distribuição De Probabilidade -Weibullunclassified
“…O treinamento e aplicação das redes ao conjunto de validação foram realizados com 10 repetições, onde no início de cada treinamento eram utilizados pesos iniciais aleatórios nas conexões dos neurônios da rede. RESULTADOS E DISCUSSÃO A distribuição média da probabilidade observada por classe de diâmetro apresentou forma exponencial negativa (J invertido), sendo as classes de menores diâmetros com maior probabilidade de ocorrência dos indivíduos, típica de florestas inequiâneas (NEELO et al, 2015;JIMENEZ et al, 2016). Conforme esperado, as classes diamétricas inferiores apresentaram maior amplitude de valores de probabilidade em relação às classes superiores, no entanto, quando é feita a razão pela média da classe, nota-se maior variação nestas últimas (Figura 2).…”
Section: Função De Distribuição De Probabilidade -Weibullunclassified
“…The selected areas were then grouped into four categories, according to fallow age: young fallows (range 7-8 yrs), medium-aged fallows (range [10][11][12][13][14] were divided into ten 100 m 2 subplots [33]. A total of forty plots were surveyed, corresponding to ten mature stands and ten in each of the fallow stages.…”
Section: Site Selection and Data Collectionmentioning
confidence: 99%
“…The rapid growth of human population in rural areas of Africa and increasing needs for food production have caused the shortening of fallow periods of abandoned fields and people to encroach into new areas that have not been subjected to agriculture before [12]. The increasing demands of the rapidly growing human population have led to land scarcity, and the remaining forests are being increasingly over utilized, far beyond their capacity for regeneration [13]. This process, as a whole, seriously impacts forest biodiversity patterns, for example, species richness and composition [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The species, family and genera richness values of woody species (44 spp., 17 families and 26 genera) recorded in this study were higher than those reported from studies in Shorobe (41 spp., 15 families and 23 genera), Maun (area exclosure in Island Safari Lodge, 33 spp., 13 families and 20 genera) and Xobe (27 spp., 10 families and 24 genera) villages (Neelo et al, 2013;Neelo et al, 2015) as well as in an area exclosure of more than 10 years (32 spp., 12 familes and 19 genera) and open area adjacent the area exclosure (24 spp., 10 familes and 15 genera) in Maun (Teketay et al, 2016) in northern Botswana, and in Shekole (18 spp.) and Guba (23 spp.)…”
Section: Discussionmentioning
confidence: 99%